Effect of Poly(γ-glutamic acid) on the Physiological Responses and Calcium Signaling of Rape Seedlings (Brassica napus L.) under Cold Stress - Lei, Peng; Xu, Zongqi; Ding, Yan; Tang, Bao; Zhang, Yunxia; Li, Huashan; Feng, Xiaohai; Xu, Hong (Journal of agricultural and food chemistry, 2015)
Cold stress adversely affects plant growth and development. Poly(γ-glutamic acid) (γ-PGA) is a potential plant growth regulator that may be an effective cryoprotectant that prevents crops from damage during cold weather. In this study, the effects of γ-PGA on the physiological responses of rape seedlings subject to cold stress were investigated using hydroponic experiments. We determined that the malondialdehyde content was decreased by 33.4% and the proline content was increased by 62.5% by γ-PGA after 144 h under cold stress. Antioxidant enzymes activities were also evidently enhanced after treatment with γ-PGA. These responses counteracted increases in the fresh weight and chlorophyll content of rape seedlings, which increased by 24.5 and 50.9%, respectively, after 144 h, which meant that growth inhibition caused by cold was mitigated by γ-PGA. Our results also showed that γ-PGA also regulated Ca2+ concentrations in the cytoplasm and calcium-dependent protein kinases, which are associated with cold resistance. In conclusion, we suggest that the Ca2+/CPKs signal pathway is involved in the γ-PGA-mediated enhancement of cold resistance in rape seedlings.